Measurement of the rapidity and transverse momentum distributions of Z bosons in pp collisions at √(s)=7TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
Measurements of the normalized rapidity (y) and transverse-momentum (q T) distributions of Drell-Yan muon and electron pairs in the Z-boson mass region (60